PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI UNTUK MENINGKATKAN KINERJA PEGAWAI - Ferry Yulian (KINERJA, 2015)
This study aims to determine the influence of organizational culture and job satisfaction on organizational commitment to improving employee performance (the study of the Agency for Family Planning and Family Welfare Samarinda). The data used are primary data with 83 respondents. SEM analysis tool with SmratPLS program. Results found (1) The better the culture of the organization will improve employee performance. (2) Cultural organizations are getting better will give higher job satisfaction for employees. (3) Improved organizational culture that better will strengthen employee commitment to the organization, (4) Increased job satisfaction will improve employee performance. (5) Increased job satisfaction will strengthen the organization's commitment. (6) Increasing organizational commitment to employees will improve employee performance. (7) The better the organizational culture will indirectly increase the performance of an employee if the employee commitment to the organization increases. (8) Cultural organizations will indirectly improve the performance of employees, if the job satisfaction of employees increased to the organization. (9) Increased job satisfaction, will indirectly increase the performance of an employee if the employee commitment to the organization increases.Â Keywords: Organizational Culture, Job Satisfaction, Organizational Commitment, Employee Performance and Agency for Family Planning and Family Welfare Samarinda